2011
DOI: 10.1590/s1413-70542011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Fixação biológica de nitrogênio e teores foliares de nutrientes na soja em função de doses de molibdênio e gesso agrícola

Abstract: RESUMOA competitividade econômica da soja brasileira no mercado mundial se deve, em grande parte, aos benefícios da fixação biológica do nitrogênio na cultura. O trabalho foi conduzido a campo, sob sistema plantio direto, em condição de sequeiro, no Município de Maracaju-MS, com o objetivo de avaliar a nodulação, o crescimento, nutrição mineral e produtividade de grãos da soja submetida a diferentes doses de gesso agrícola e molibdênio. Foi utilizado o delineamento experimental de blocos ao acaso, com cinco re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
7
0
3
Order By: Relevance
“…The increase in Ca and S in the leaf contents was expected since this corrective is a source of these nutrients. Increases in Ca and S concentrations in soybean leaves were also observed in other studies (CAIRES et al, 2003;JORIS;CHURKA, 2011;GELAIN et al, 2011).…”
Section: Resultssupporting
confidence: 85%
“…The increase in Ca and S in the leaf contents was expected since this corrective is a source of these nutrients. Increases in Ca and S concentrations in soybean leaves were also observed in other studies (CAIRES et al, 2003;JORIS;CHURKA, 2011;GELAIN et al, 2011).…”
Section: Resultssupporting
confidence: 85%
“…A decrease in Mg concentration in corn leaf tissue after PG application was reported also by Raij et al (1998) and Caires et al (2004). For wheat, Caires et al (2002) reported no effect of PG application on Mg leaf concentration, while Rampim et al (2011) also observed a decline in leaf Mg, and the studies of Caires et al (2003; and Gelain et al (2011) found increasing PG application rates related to a decrease in Mg concentration in soybean leaves.…”
Section: Macronutrient Plant Leaf Tissue Concentrationsmentioning
confidence: 53%
“…This effect is related to the Mo content contained in the product, 23.54%. According to Gelain et al (2011), Mo is an essential element for the activity of nitrate reductase, which reduces nitrate to nitrite, which is directly related to the supply of the N to the plant. According to the authors, the application of molybdenum fertilizer via seed treatment is more indicated because it is more practical and effective in relation to the soil or foliar applications.…”
Section: Methodsmentioning
confidence: 99%